2005
DOI: 10.1124/jpet.105.087536
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Acetate Supplementation Therapy for Canavan Disease: Glyceryl Triacetate Administration Increases Acetate, but NotN-Acetylaspartate, Levels in Brain

Abstract: Canavan disease (CD) is a fatal genetic neurodegenerative disorder caused by mutations in the gene for aspartoacylase, an enzyme that hydrolyzes N-acetylaspartate (NAA) into L-aspartate and acetate. Because aspartoacylase is localized in oligodendrocytes, and NAA-derived acetate is incorporated into myelin lipids, we hypothesize that an acetate deficiency in oligodendrocytes is responsible for the pathology in CD, and we propose acetate supplementation as a possible therapy. In our preclinical efforts toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 42 publications
(45 reference statements)
4
63
1
Order By: Relevance
“…Esterases present in most tissues of the body can cleave the acetate moieties, generating free acetate. Dosing experiments in mice demonstrated that GTA was 10 to 20 times more effective at delivering acetate to the brain than calcium acetate, and that it was well tolerated by developing mice (Mathew et al, 2005). If substantially elevated levels of acetate can be maintained in oligodendrocytes through dietary acetate supplementation during postnatal myelination, this should theoretically correct the acetate deficiency that occurs in Canavan disease.…”
Section: Potential Acetate Supplementation Therapy For Canavan Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Esterases present in most tissues of the body can cleave the acetate moieties, generating free acetate. Dosing experiments in mice demonstrated that GTA was 10 to 20 times more effective at delivering acetate to the brain than calcium acetate, and that it was well tolerated by developing mice (Mathew et al, 2005). If substantially elevated levels of acetate can be maintained in oligodendrocytes through dietary acetate supplementation during postnatal myelination, this should theoretically correct the acetate deficiency that occurs in Canavan disease.…”
Section: Potential Acetate Supplementation Therapy For Canavan Diseasementioning
confidence: 99%
“…Currently there is no effective treatment available for restoring proper myelination and motor function. The pathogenic mechanisms operative in Canavan disease currently remain a matter of debate, but it has been proposed that the etiology involves a lack of NAA-derived acetate, which is required for some portion of myelin lipid synthesis during postnatal axonal myelination (Hagenfeldt et al, 1987;Kirmani et al, 2002;Madhavarao et al, 2005;Mathew et al, 2005;Mehta and Namboodiri, 1995;Namboodiri et al, 2006b;Namboodiri et al, 2006a). Under this hypothesis, infants born with Canavan disease are normal at birth because ASPA activity is not critical until myelin synthesis is dramatically increased shortly after birth.…”
Section: Naa Breakdown and Myelin Lipid Synthesismentioning
confidence: 99%
“…Intragastric administration of equivalent amounts of CA or GTA to 21-day-old C57BL/6 mice showed GTA to raise CNS Ac levels much more effectively 5 and to have fewer adverse effects than CA, although both were found to be reasonably safe (Mathew et al, 2005;Namboodiri et al, 2006).…”
Section: Supplementation Of Acmentioning
confidence: 99%
“…Other studies have focused on the "Ac-myelin-lipid" hypothesis and attempted to restore myelination through Ac-supplementation (Arun et al, 2010;Madhavarao et al, 2009;Mathew et al, 2005;Namboodiri et al, 2006;Segel et al, 2011) (Table 2). To this end, calcium Ac (CA) and glyceryl triacetate (GTA) have both been tested in their ability to deliver Ac to the CNS (Mathew et al, 2005;Namboodiri et al, 2006).…”
Section: Supplementation Of Acmentioning
confidence: 99%
See 1 more Smart Citation